The Routledge handbook of gender and violence - Lombard, Nancy (Routledge, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences

Les Amériques créatives: regards croisés sur les discours et les pratiques - Pujol, Charlotte; Doré, Émilie; Drouilleau, Félicie; Villafuerte, Susana; Tinteroff Gil, Vanessa (L'Harmattan, 2017)
"Des civilisations précolombiennes à l'American Way of Life, les A mériques ont constitué un espace propice aux mythes et aux utopies. Terres de migrations, parfois forcées, elles sont constituées de multiples lieux de rencontres, de conflits, d'échanges culturels. Aujourd'hui les phénomènes d'innovation technologique, identitaire ou politique témoignent du fait que les Amériques, du Nord au Sud, demeurent un terreau de créativité. La créativité repose sur la capacité des acteurs à imaginer un autre cadre que celui dans lequel ils sont immergés. Aussi cet ouvrage s'attarde-t-il sur les discours et les pratiques individuels ou collectifs, discrets ou médiatisés, improvisés ou programmés qui participent à la fabrique des espaces et des sociétés. La diversité des regards et des situations analysées se traduit par la multi disciplinarité de ces pages. Sociologues, anthropologues, historiens, juristes, géographes, spécialistes de la littérature, du cinéma, du théâtre ou de la musique proposent des analyses ancrées dans la réalité ; leurs points de vue sont autant d'illustrations des processus créatifs. Il ne s'agissait pas là de chercher une improbable exhaustivité, mais bien plutôt de tenter de mettre en lumière la façon dont la force créative des individus et des groupes jalonne l'histoire et le devenir des nations américaines. C'est donc un kaléidoscope qui est proposé aux lecteurs, une diversité d'approches qui les font voyager de l'Alaska au Brésil."–Page 4 de la couverture
Le chapitre Nagels, Nora, 2017, « Créativité clientéliste des organisations de femmes populaires liées à l’alimentation à Lima », a été donné en lecture au cours POL4022.
Keywords: DIG; agriculture; amériques; anthropologie; arts; care; corps; cours; création; danse; discipline; environnement; géographie; musique; pol4022; premier cycle; régions géographiques; sciences humaines; sociologie; thématiques

Les Autochtones au Canada: espaces et peuples en mutation - Desbiens, Caroline; Hirt, Irène (L'Information géographique, 2012)
Alors que les questions relatives à l’autochtonie ont longtemps été le domaine de l’anthropologie, nous assistons ces dernières années à un décloisonnement des recherches. La géographie participe activement à cette mouvance, notamment par la richesse de sa boîte à outils en ce qui concerne les questions de paysage, ressources, environnement et gouvernance territoriale. En commençant par un survol des aires culturelles autochtones en Amérique, nous proposons dans cet article d’identifier trois thèmes dominants en ce qui a trait aux espaces de l’autochtonie contemporaine au Canada : la gouvernance, les savoirs, et l’urbanité.
Keywords: amériques; approches et analyses; cours; discipline; géographie; har4600; histoire et politique; pol4105; premier cycle; premières nations; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques

Sustainable development, water resources management and women's empowerment: The Wanaraniya water project in Sri Lanka - Aladuwaka S.; Momsen J. (Gender and Development, 2010)
Water is one of the most important natural resources, and its effective management is essential given its scarcity. In rural Sri Lanka, the management of available water resources needs special attention because investment for water resource improvement is hard to obtain, and water itself is relatively scarce in the drier areas of the country. The Wanaraniya Water Project pipes water 6.5km from its source to individual houses in the village, saving women daily time and effort. The project is founded on commitments to community participation and the adoption of local knowledge. It was initiated by women, and has been operated and managed by them for the last six years. This study argues that the project can serve as a model for better planning of water management, and focuses on the unique strategies and innovative methods that have been used. In particular, it shows the impact of involvement in the project on women’s empowerment. The implementation of the project has helped women to improve their leadership qualities, confidence, self-reliance, and gain more power in the community through their successful establishment of a village water supply.
Keywords: approches et analyses; asie; cours; discipline; développement; développement participatif; environnement; géographie; histoire et politique; justice sociale; pol4022; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sri lanka; thématiques; études de genres

Critical geographies and the uses of sexuality: deconstructing queer space - Oswin, Natalie (Progress in Human Geography, 2008)
Scholarship on queer geographies has called attention to the active production of space as heterosexualized and has levelled powerful critiques at the implicit heterosexual bias of much geographical theorizing. As a result, critical geographers have begun to remark upon the resistance of gays, lesbians and other sexual subjects to a dominant heterosexuality. But such a liberal framework of oppression and resistance is precisely the sort of mapping that poststructuralist queer theory emerged to write against. So, rather than charting the progress of queer geographies, this article offers a critical reading of the deployment of the notion of `queer space' in geography and highlights an alternative queer approach that is inseparable from feminist, materialist, postcolonial and critical race theories.
Keywords: LGBTQIA2+; approches et analyses; architecture; cours; discipline; espace; géographie; hétéronormativité; premier cycle; queer; résistance; sciences humaines; soc2014; thématiques

Suzanne MacKenzie Memorial Lecture conceptually unclad: feminist geography and Aboriginal peoples * - Peters, Evelyn J. (The Canadian Geographer, 2004)
This paper argues that feminist geography can provide some useful lessons in an attempt to increase Aboriginal peoples' representation in geography. It asks the question: How can we use the example of feminist geography to think about a geography that is more inclusive of Aboriginal people? The paper focuses on the issues of content in teaching, drawing on examples from urban and social geography, and on methodological challenges, especially the issue of reflexivity. Feminist geographer Suzanne Mackenzie argued that an emerging feminist geography left the discipline ‘conceptually unclad’, challenging scholars to consider new theoretical frameworks and new perspectives. I argue that emphasising the geographies of Aboriginal people also enriches geography, including feminist geography.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; démographie; environnement; féminisme autochtone; géographie; géographie féministe; géographie urbaine; histoire et politique; méthodologie; pol4105; premier cycle; périodes historiques; sciences humaines; thématiques

Transnational migration theory in population geography: gendered practices in networks linking Canada and India - Walton-Roberts, Margaret (Population, Space and Place, 2004)
Geographers have recently suggested that transnational migration theory can contribute to the development of a critical population geography. What might such a critical population geography look like? In this paper I explore this in three ways. Firstly I offer some comments on why geographers have been slow to adopt a transnational focus on migration, and secondly I examine how gender has been underplayed in transnational literature. Thirdly I draw upon some examples from research on transnational immigrant networks between Canada and India. I focus on the specifics of Punjabi marriage migration networks to demonstrate how the practice of spousal selection has become globalised for certain diasporic communities. These examples offer a preliminary illustration of what a critical population geography, attuned to issues of gendered transnational processes, might contribute to current debates. Copyright © 2004 John Wiley & Sons, Ltd.
Keywords: amériques; approches et analyses; asie; canada; cours; discipline; géographie; histoire et politique; inde; mariage; mariages transnationaux; migration; premier cycle; punjab; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques

Les femmes autochtones au Canada : profil statistique d'après le recensement de 2006 - Affaires autochtones et développement du Nord Canada (2002)
Sommaire : points saillants de la situation des femmes autochtones au Canada. Structure de la population et lieu de résidence : •• En 2006, les femmes autochtones en Ontario représentaient environ 11 % de l’ensemble de la population d’identité autochtone. 31 % des femmes autochtones vivaient dans les provinces de l’Ouest (Manitoba, Saskatchewan, Alberta et Colombie‑Britannique). •• En 2006, l’âge médian de la population autochtone était de 27 ans, contre 40 ans pour la population non autochtone, une différence de 13 ans. Les résultats de l’étude révèlent que chez les Indiens inscrits vivant dans les réserves, un peu plus de femmes (44 %) que d’hommes (35 %) étaient âgés de 19 ans et moins. En comparaison, le pourcentage des Indiens inscrits vivant hors réserve âgés de 19 ans et moins était un peu plus élevé tant chez les femmes (45 %) que chez les hommes (43 %). De plus, de tous les groupes d’identité autochtone, c’est chez la population inuite féminine (49 %) et masculine (46 %) que se trouvait la proportion la plus importante des 19 ans et moins. •• La population féminine autochtone vieillit, quoique à un rythme plus lent que la population féminine non autochtone. En 2006, les femmes de 60 ans et plus représentaient plus de 7 % de l’ensemble de la population d’identité autochtone. Utilisation et connaissance des langues •• Les résultats de l’étude révèlent que la majorité des femmes autochtones, soit 73 %, ont appris l’anglais comme langue maternelle, tandis que seulement 16 % ont d’abord appris une langue autochtone et 8 %, le français. La proportion de filles et de femmes autochtones dont la langue maternelle est une langue autochtone (langue amérindienne ou inuktitut) est relativement faible dans les groupes d’âge plus jeunes, et plus élevée dans les groupes d’âge plus âgés. L’anglais prend donc plus d’importance que les langues autochtones et le français au fil du temps. •• La proportion de la population de langue maternelle autochtone est plus élevée chez les Inuites. Un plus grand nombre de femmes inuites de tous les groupes d’âge, soit 65 %, indiquent que l’inuktitut est leur langue maternelle, contre 32 % pour l’anglais. Chez 28 % des Indiennes inscrites, la langue maternelle est une langue autochtone; la proportion est beaucoup plus faible chez les Métisses, à 3 %. •• La vaste majorité (75 %) des Autochtones parlent principalement l’anglais à la maison, alors que 16 % parlent une langue autochtone et 5 %, le français. En outre, 29 % des membres des Premières nations affirment qu’ils peuvent parler une langue autochtone suffisamment bien pour tenir une conversation. La proportion est cependant beaucoup plus élevée chez les membres des Premières nations vivant dans les réserves. En 2006, la moitié des membres des Premières nations vivant dans les réserves (51 %) pouvaient s’exprimer dans une langue autochtone, contre 12 % de ceux qui vivaient hors réserve. Les langues des Premières nations les plus répandues en 2006 étaient le cri (87 285), l’ojibway (30 255), l’oji‑cri (12 435) et le montagnais‑naskapi (11 080).
Last Modified: 2013-04-03
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; démographie; famille; femmes* autochtones; géographie; histoire et politique; intersectionnalité; langue; langues autochtones; maternité; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; thématiques; transmissions; éducation; étude démographique

Mapping desire: geographies of sexualities - Bell, David; Valentine, Gill (Routledge, 1995)
This is the first book to explore sexualities from a geographical perspective. The nature of place and notions of space are of increasing centrality to cultural and social theory. Mapping Desire presents the rich and diverse world of contemporary sexuality, exploring how the heterosexual body has been appropriated and resisted on the individual, community and city scales. The geographies presented here range across Europe, America, Australasia, Africa, the Pacific and the imaginary, cutting across city and country and analysing the positions of gay men, lesbians, bisexuals and heterosexuals. The contributors ring different interests and approaches to bear on theoretical and empirical material from a wide range of sources. The book is divided into four sections: cartographies/identities; sexualised spaces: global/local; sexualised spaces: local/global; sites of resistance. Each section is separately introduced. Beyond the bibliography, an annotated guide to further reading is also provided to help the reader map their own way through the literature.
Le texte de Binnie, Jon. 1995. « Trading places : consumption, sexuality and the production of queer space. » figure dans la bibliographie du cours SOC2014.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; géographie; hétéronormativité; hétérosexisme; premier cycle; queer; sciences humaines; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques